2013
DOI: 10.1523/jneurosci.5052-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Dendritic Arborization andIn VivoFiring Patterns of Parvalbumin-Expressing Basket Cells in the Hippocampal Area CA3

Abstract: Hippocampal CA3 area generates temporally structured network activity such as sharp waves and gamma and theta oscillations. Parvalbumin-expressing basket cells, making GABAergic synapses onto cell bodies and proximal dendrites of pyramidal cells, control pyramidal cell activity and participate in network oscillations in slice preparations, but their roles in vivo remain to be tested. We have recorded the spike timing of parvalbumin-expressing basket cells in areas CA2/3 of anesthetized rats in relation to CA3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
92
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 107 publications
8
92
2
Order By: Relevance
“…PV + interneurons have multiple dendrites which often cross layers (17)(18)(19)(20). This will permit PV + interneurons to receive input from different afferent pathways, such as feedforward and feedback pathways.…”
Section: Morphological Properties and Connectomics Of Pvmentioning
confidence: 99%
See 2 more Smart Citations
“…PV + interneurons have multiple dendrites which often cross layers (17)(18)(19)(20). This will permit PV + interneurons to receive input from different afferent pathways, such as feedforward and feedback pathways.…”
Section: Morphological Properties and Connectomics Of Pvmentioning
confidence: 99%
“…This will permit PV + interneurons to receive input from different afferent pathways, such as feedforward and feedback pathways. The cumulative dendritic length of single PV + interneurons ranges from 3.1 to 9 mm (17)(18)(19)(20). Long dendrites allow PV + interneurons to sample input from a large population of principal cells.…”
Section: Morphological Properties and Connectomics Of Pvmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodic perisomatic inhibition has been held responsible for the generation of the high-frequency components and the phaselocking of neuronal activity [3], but no convincing data are available about the initiation of SWRs, although the SWR state is considered an "off-line" state of the hippocampus [1 2]. To uncover the participation of different types of neurons in SWR generation, several in vivo [28][29][30][31][32][33][34] and in vitro [35][36][37] studies have examined the firing characteristics of identified neuron types (summarized in [38]). Mostly similar relative firing patterns were found for the examined cell types, but there were some contradictory results, which might have arisen from differences between the CA1 and the CA3 area, and most importantly from anaesthetized compared to freely moving animals or in vitro slices.…”
Section: Introductionmentioning
confidence: 99%
“…While it is clear that basket cells inhibit their target neurons, the effect of axo-axonic cells is still debated and it can be either excitatory (Szabadics et al, 2006) or inhibitory (Glickfeld et al, 2009). In addition, the three perisomatic interneuron groups are active at different times and show different firing patterns during network oscillations in vivo (Klausberger et al, 2003;Klausberger et al, 2005;Tukker et al, 2007;Lasztóczi et al, 2011;Lapray et al, 2012;Tukker et al, 2013) and also in in vitro preparations Hájos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%